The Holy Spirit in African Christianity - Reed, Rodney L.; Ngaruiya, David K. (Langham, 2022)
The identity and nature of the Holy Spirit has long been a critical – and often divisive – topic among Christians. Yet it is one with which we must continue to grapple if we are to grow in our understanding of the personhood of God, the calling of the church and the life of the believer. The seventh volume drawn from the annual conference of the Africa Society of Evangelical Theology, this collection of essays addresses questions of pneumatology against the rich background of African church history. African theologians explore centuries of Christian understanding, from the writings of Augustine to the doctrine of African Instituted Churches, and examine the impact of pneumatological belief upon the life and worship of the believer. Serving as a corrective on pneumatological heterodoxies while making space for both the diversity and unity of the African church, this volume provides a powerful reminder of the centrality of the Holy Spirit to Christian doctrine and praxis.
paid